Advances in the application of tumor vaccines and combination strategies: new perspectives in lung cancer treatment - Sun, Lei; Zhao, Qi; Miao, Liyun (Frontiers in Immunology, 2026)
Lung cancer remains one of the most prevalent and lethal malignancies globally and its treatment has consistently been a focal point of research in the medical field. The emergence of immunotherapies such as immune checkpoint inhibitors has brought about a new understanding of vaccine treatment for tumors. Tumor vaccines induce anti-tumor immune responses by targeting tumor-associated antigens or specific neoantigens. In recent years, advancements in vaccine technology, such as neoantigen screening, refinement of vector systems, and optimization of adjuvants, have significantly propelled the development of personalized tumor vaccines, thereby endowing lung cancer vaccines with substantial therapeutic potential. Furthermore, studies have demonstrated that the integration of tumor vaccines with immune checkpoint inhibitors, chemotherapy, and other therapeutic modalities can produce synergistic anti-tumor effects. This article reviews the latest progress in lung cancer vaccines, elucidates current combination treatment strategies supported by preclinical and clinical evidence, and explores their translational potential for clinical application.